Buspirone treatment of cannabis dependence: A randomized, placebo-controlled trial. (1st November 2015) - McRae-Clark, Aimee L.; Baker, Nathaniel L.; Gray, Kevin M.; Killeen, Therese K.; Wagner, Amanda M.; Brady, Kathleen T.; DeVane, C. Lindsay; Norton, Jessica
Highlights: The efficacy of buspirone for treatment of cannabis dependence was evaluated. Buspirone provided no advantage over placebo in reducing cannabis use. Women randomized to buspirone had worse cannabis use outcomes. Abstract: Background: The purpose of this study was to evaluate the efficacy of buspirone, a partial 5-HT1A agonist, for treatment of cannabis dependence. Methods: One hundred seventy-five cannabis-dependent adults were randomized to receive either up to 60 mg/day of buspirone ( n = 88) or placebo ( n = 87) for 12 weeks combined with a brief motivational enhancement therapy intervention and contingency management to encourage study retention. Cannabis use outcomes were assessed via weekly urine cannabinoid tests. Results: Participants in both groups reported reduced cannabis craving over the course of the study; however, buspirone provided no advantage over placebo in reducing cannabis use. Significant gender by treatment interactions were observed, with women randomized to buspirone having fewer negative urine cannabinoid tests than women randomized to placebo ( p = 0.007), and men randomized to buspirone having significantly lower creatinine adjusted cannabinoid levels as compared to those randomized to placebo ( p = 0.023). An evaluation of serotonin allelic variations did not find an association with buspirone treatment response. Conclusions: Buspirone was not more efficacious than placebo in reducing cannabis use. Important gender differences were noted, with women having worse cannabis use outcomes with buspirone treatment. Considerations for future medication trials in this challenging population are discussed.